2017
DOI: 10.1016/j.jot.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar degenerative spondylolisthesis epidemiology: A systematic review with a focus on gender-specific and age-specific prevalence

Abstract: SummaryThe epidemiology of lumbar degenerative spondylolisthesis (DS) remains controversial. We performed a systematic review with the aim of gaining a better understanding of the prevalence of DS in the general population. The results showed that the prevalence of DS is very gender- and age-specific. Few women and men develop DS before they are 50 years old. After 50 years of age, both women and men begin to develop DS, with women having a faster rate of development than men. For elderly Chinese (≥ 65 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
158
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(174 citation statements)
references
References 133 publications
(179 reference statements)
8
158
1
7
Order By: Relevance
“…The prevalence of spondylolisthesis shows a female predominance, with studies showing a female: male (F:M) prevalence ratio of 1.3:1. 13 In our study of 40 patients, we observed a higher male predominance. 24 patients (60%) were male and 16 patients (40%) were female.…”
Section: Discussionsupporting
confidence: 44%
“…The prevalence of spondylolisthesis shows a female predominance, with studies showing a female: male (F:M) prevalence ratio of 1.3:1. 13 In our study of 40 patients, we observed a higher male predominance. 24 patients (60%) were male and 16 patients (40%) were female.…”
Section: Discussionsupporting
confidence: 44%
“…increased biconcavity), 6 increased wedge of thoracic vertebral bodies, and osteoporotic fracture. Intervertebral disc 7 degeneration can progress to disc herniation, spinal canal stenosis, and, in conjunction with facet 8 joint arthrosis, degenerative spondylolisthesis [1][2][3][4][5]. Histology studies show disc degeneration 9 becomes apparent in men in the second decade of life, almost a decade earlier than in women 10 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Spondylolisthesis and spondylodiscitis are nowadays common spinal pathologies in the neurosurgery department [1,2]. Although spondylodiscitis is rare in the general population [3], its current increasing incidence is deemed to be multifactorial, due to the growth of ageing people and chronic diseases, improvement of diagnostic tools, general use of indwelling intravascular catheters, and immunosuppressive therapies [4].…”
Section: Introductionmentioning
confidence: 99%